STRATEGI PENINGKATAN KOMPETENSI PENGAWAS SEKOLAH PADA UNIT PELAKSANA TUGAS DINAS (UPTD)-II PENDIDIKAN DI KECAMATAN SIMEULUE BARAT-ALAFAN KABUPATEN SIMEULUE - Rona Samdoni, Murniati AR, Bahrun (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: The key to the success of a school is hugely influenced by the quality of supervision. Supervisors’ capacity is one of the determining factors in the quality improvement of education. This study describes the school supervisors’ capacity building strategies at Technical Implementing Unit of Education Office (UPTD) - II in the Sub-district of Simeulue Barat-Alafan, Simeulue. This is a descriptive research using qualitative approach. Data ware gathered using observation, interviews, and documentation techniques. The subject of this study are Head of UPTD, Supervisor Coordinator, and Head of division for program development at the local education office. The results of the research show that (1) the capacity building program is written by the head of program development division before new academic year starts (June - July) with the following activities: material selection, methods, INSTRUMENs, and stages for supervisor recruitment plan, information sessions on the implementation of academic and managerial supervision, supervisors’ participation in trainings, continuing education, and documented competition for best performing supervisors. (2) Some efforts have been made for school supervisors’ capacity building,including direct coaching which is in collaboration withthe Education Office and KORWASDA (Local Supervisor Coordinator), selection of school supervisor candidates in line with existing regulations, inviting supervisors to participate in various training and workshops, providing opportunities for further study, and giving awards to supervisors with best performance. (3) Evaluation of the success of school supervisor capacity building program has not acquired a valid INSTRUMEN. Assessment is conducted based on merely subjective and very abstract evaluation and prediction. (4) Some challenges and obstacles experienced include limited human resources from the instructors’ part, and limited opportunity for training.Keywords: Strategy, Interest, and School SupervisorAbstrak: Kunci keberhasilan suatu sekolah sangat dipengaruhi oleh kualitas supervisi pendidikan. Kompetensi pengawas merupakan salah satu faktor peningkatan mutu pendidikan. Penelitian ini mendeskripsikan strategi peningkatan kompetensi pengawas sekolah pada Unit Pelaksana Tugas Dinas (UPTD)-II Pendidikan di Kecamatan Simeulue Barat-Alafan Kabupaten Simeulue. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif, teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Subjek penelitian adalah Kepala UPTD, Koordinator Pengawas Sekolah, dan Kabid. Bina Program. Hasil penelitian menunjukkan bahwa: (1) Program peningkatan kompetensi pengawas sekolah disusun oleh Kabid. Bina Program yang dilaksanakan  sebelum ajaran baru bulan Juni sampai dengan bulan Juli dengan kegiatan program diantaranya: penentuan materi, metode, INSTRUMEN, dan tahapan untuk rencana kegiatan rekruitmen pengawas sekolah, memberikan pemahaman kepada pengawas mengenai tatacara pelaksanaan supervisi akademik maupun manajerial, mengikutsertakan pengawas mengikuti pelatihan/penataran, pendidikan lanjut, lomba pengawas sekolah berprestasi terdokumentasi. (2) Implementasi peningkatan kompetensi pengawas sekolah yang telah dilakukan antara lain melakukan pembinaan langsung bekerja sama dengan Dinas Pendidikan dan KORWASDA, melakukan seleksi calon pengawas sekolah sesuai dengan peraturan yang berlaku, mengikutsertakan pengawas dalam berbagai kegiatan pelatihan/penataran dan workshop. (3) Evaluasi keberhasilan peningkatan kompetensi pengawas sekolah belum memiliki INSTRUMEN keberhasilan yang valid. Penilaian keberhasilan program hanya dilaksanakan berdasarkan perkiraan yang sangat abstrak. (4) Kendala yang dialami dalam upaya peningkatan kompetensi pengawas sekolah antara lain keterbatasan biaya, terbatasnya sumber daya manusia pelatih/instruktur, serta terbatasnya peluang pelatihan/penataran.Kata Kunci: Strategi, Kompetensi, dan Pengawas Sekolah